Evaluation of Thyroid Profile and Liver Function Tests in Pregnant Women of Mirpur AJK (Medical Forum Monthly, 2023)
Objective: The objective of this study to evaluate thyroid profile and liver function tests in pregnant women of Mirpur AJKStudy Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology MBBS Medical College Mirpur AJK and Mohi-Ud-Din Islamic Medical College, Mirpur AJ&K from March 2021 to December 2022.Materials and Methods: The study encompassed a total of 300 adult participants, consisting of 150 pregnant women and 150 non-pregnant females. The selection of 150 pregnant women was based on specific inclusion and exclusion criteria.Comprehensive patient profiles were established by conducting brief medical histories and clinical examinations. Pertinent information such as gestational period, height, weight, blood pressure, prior medication history, and relevant clinical details were documented. The participation of each patient was secured through informed verbal consent. Subsequently, blood specimens were collected from the participants. The analysis of these blood samples was performed at the Biochemistry Department of MBBS Medical College in Mirpur AJKResults: The mean Fasting Blood Glucose value for the case group was found to be 92.02 (SD±115.04), whereas the control group displayed a mean value of 78.60 (SD±8.88). Importantly, a remarkably significant statistical outcome emerged from this analysis (p Value < 0.000), underscoring a substantial distinction between the two groups. .Furthermore, the investigation extended to the assessment of serum Bilirubin levels within both the case and control cohorts. In the case group, the mean serum Bilirubin value was observed to be 0.99 (SD±0.28), while the control group manifested a mean value of 0.78 (SD±0.19).Conclusion: Any disruption in these functions can pose significant risks to both the mother and the fetus. Consequently, proper management of hepatic and thyroid function is essential to ensure the well-being of both the mother and the baby.